Investment objectives and factors that influence the disappearance of Spanish mutual funds - Barberà-Mariné, M. Glòria; Fabregat-Aibar, Laura; Terceño, Antonio (Journal of Business Economics and Management, 2020)
This paper analyses which variables influence the disappearance of mutual funds in the Spanish market and whether these variables vary depending on the investment objectives. The following variables are tested: age, size, investment flows, return, volatility, Sharpe ratio, Morningstar rating, and fund family. The Kaplan-Meier estimator and an extension of the Cox model, the Andersen-Gill model are used and the results indicate that the impact of some variables on survival capacity is different depending on the fund’s investment objectives. The originality of this article is twofold. The analysis of disappearance takes the investment objectives of the mutual funds into account and a new variable, the Morningstar rating, is introduced. Moreover, no previous study examines survival capacity in the Spanish market according to different investment objectives. In Spain, mutual funds are highly concentrated because most of them are in the hands of a small number of banks who also control the country’s largest fund families. This characteristic not only makes the Spanish market an interesting one for analysis, but it also means that the results of this paper are significant for mutual fund investors.